Periferias esquerda e direita: assimetrias - Duarte, Inês (2018)
In this paper, we compare the right and the left peripheries in European Portuguese, presenting evidence for the analysis of the right-peripheral material as elliptical in nature. We discuss several analyses for the right periphery in light of European Portuguese data, including: (i) data from spontaneous adult (child-directed) speech (5 adults, 29,398 utterances) annotated in the corpus Santos (Santos, 2006/2009; Santos et al., 2014) and (ii) experimental data (41 children aged between 3;5 and 6;3, and 30 adults) on the comprehension of topicalizations, clitic-left dislocations, post-focal subjects on the right periphery, and subject-verb inversions with a focused subject (Abalada, 2011).